COURSE STATUS OF MUSIC TEACHING PROGRAMS IN THE FIELD OF MUSIC TECHNOLOGIES - ASMA İPEKÇİLER, Beste; ÖZTOSUN ÇAYDERE, Öznur (Online journal of music sciences, 2022)
Bu çalışma müzik öğretmenliği programı olan üniversitelerin ders paketleri incelenerek ilgili bölümlerde müzik teknolojileri dersinin mevcut olma durumunu, ders saat dağılımını ve zorunlu/seçmeli olma durumunu ortaya koyma amacını taşımaktadır. Araştırma nitel veri toplama tekniklerinin kullanıldığı betimsel bir çalışmadır. Bu araştırmanın evrenini öğrencisi olan 32 üniversitedeki müzik öğretmenliği programı oluşturmaktadır. 2018 öncesi ve sonrası bilgi paketi ve müzik teknolojileri dersi olan 7 üniversite örneklem grubunu oluşturmaktadır. Veriler doküman inceleme yoluyla toplanmış ve içerik analizi ile çözümlenmiştir. Yapılan inceleme sonucunda üniversitelerde 2018 öncesinde daha yaygın bir şekilde müzik teknolojileri eğitimi verilirken, 2018 sonrasında dersin daha az verilmeye başlandığı, müzik teknolojileri dersinin “Bilgisayar I ve Bilgisayar II” adı altında verildiği görülmüştür. This study aims to reveal the availability of music technologies course in the relevant departments, the distribution of course hours and the compulsory/elective status of the universities by examining the course packages of the universities with music teaching programs. The research is a descriptive study in which qualitative data collection techniques are used. The universe of this research consists of music teaching programs in 32 universities with students. It constitutes the sample group of 7 universities with information package and music technologies course before and after 2018. Data were collected through document review and analyzed by content analysis. As a result of the examination, it has been seen that while music technologies education was given more widely in universities before 2018, the course started to be given less after 2018, and the music technologies course was given under the name of "Computer I and Computer II".